Developmental language disorders - Nation, K (2005)
Difficulty with language is one of the most common reasons for referral to health professionals during the pre-school years. Language difficulties are associated with many developmental disorders such as autism but for children with specific language impairment (SLI), language problems are relatively specific. SLI is a neurodevelopmental disorder with a heritable bases. Patterns of inheritence are complex suggesting multiple genes operating probabilistically alongside multiple environmental risk factors. This complexity is mirrored by a complex and heterogenous phenotype. Children with persistent language inpairment are at risk of psychosocial and behaviour problems as well as poor literacy and low educational achievement. A challenge for future work is to understand how genetic and environmental factors impinge on brain development, as well as to develop and refine methods of assessment and intervention. © 2005 Elsevier Ltd. All rights reserved.